Cooling strategies for firefighters: Effects on physiological, physical, and visuo-motor outcomes following fire-fighting tasks in the heat. (May 2022) - Fullagar, Hugh; Notley, Sean R.; Fransen, Job; Richardson, Andrew; Stadnyk, Antony; Lu, Donna; Brown, Georgia; Duffield, Rob
Abstract: Objectives: Due to the nature of firefighting, most effective cooling interventions to reduce heat strain and optimise performance are not practically viable. This study quantified the effects of two practical cooling strategies, co-designed with subject-matter experts, on physiological strain and physical, perceptual, and visuo-motor performance during simulated firefighting in the heat. Design: Randomised cross-over. Methods: On three occasions 14 firefighters completed an 80-min simulation in a hot-humid environment (32.0[0.9]°C, 59[3]%RH) including two 20-min firefighting tasks in full protective clothing, each followed by 20-min seated recovery. Recovery involved removal of protective clothing and one of three interventions – control (CON; ambient-temperature water consumption), basic (BASIC; cool-water consumption, ambient-forearm immersion/towels, fan), and advanced (ADV; ice-slushy consumption, cool-forearm immersion/ice packs, misting-fan). Thermal (core temperature) and cardiovascular (heart rate, arterial pressure) responses were measured throughout, whilst physical (handgrip/balance), visuo-motor (reaction time/memory recall) and perceptual (fatigue/thermal sensation/comfort) measures were assessed pre- and post-trial. Results: Compared to CON, core temperature was lower in BASIC and ADV following the second task (ADV: 37.7[0.4]; BASIC: 38.0[0.4]; CON: 38.3[0.4]°C) and recovery protocol (ADV: 37.5[0.3]; BASIC: 37.7 [0.3] CON: 38.3[0.4]°C). This was paralleled by lowered heart rate, rate pressure product, and thermal sensation following the recovery protocols, in the ADV and BASIC condition compared to CON (p < .05). No physical or visuo-motor outcomes differed significantly between conditions. Conclusion: Whilst these observations need to be extended to field conditions, our findings demonstrate that two novel cooling interventions developed in collaboration with subject-matter experts offered benefits for reducing thermal strain and optimising firefighter safety. Highlights: A combination of cooling methods showed significant reductions in core temperature. These results will help design education and dissemination of cooling interventions. Future research should examine visuo-motor performance as a function of heat stress.